APLIKASI PENCEGAH PENIPUAN JUAL BELI AKUN MOBILE LEGENDS BERBASIS MOBILE MENGGUNAKAN FRAMEWORK FLUTTER - Agil Fajar Dwi Prasetyo; Ade Eviyanti; Metatia Intan Mauliana (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
The internet is a phenomenon in today's era, serving not only as a medium for information sharing but also permeating the realm of online gaming, particularly Mobile Legends. This online game, playable even on low specifications, offers not only pure entertainment but also a potential avenue for trade. However, this situation can give rise to fraudulent activities due to Mobile Legends' "hackback" feature, wherein sellers can reclaim the accounts they have sold to customers. To address these issues, the researcher has developed an application that can blacklist game IDs involved in fraudulent activities, thus preventing recurring scams. In the User Acceptance Testing (UAT), this application scored 86%, falling within the "strongly agree" range. It is hoped that this application will assist parties engaged in account transactions, protecting them from unscrupulous entities and mitigating potential losses.